Branding Untirta Jawara and HITS and Green Campus Through Media Rel - Nurprapti Wahyu Widyastuti; Rahmi Winangsih; Dinda Aisah (Future Science, 2023)
Sustainable development in the field of environmentally sound education is contained in SDGs No. 4, (Quality Education), and SDGs No. 9 (industry, innovation, and infrastructure). Untirta as an agent of chanre embodies a superior Untirta with environmental insight. Untirta's branding efforts are still partial and not optimal, therefore Untirta's vision must be understood by all stakeholders and internalized in every academic community. This study aims to determine the strategy of Branding Untirta Jawara as a Healthy, Integrated, Smart and Green (HITS and Green) Campus through a Media Relations Approach. Case study research methods, data obtained through interviews, observations and Focus group discussions. In formulating, designing and building the Untirta brand begins with the implementation of an analysis of three main parties, namely: Customers (consumer audit), Competitors (competitor audit) and Internal Stakeholders (internal audit). The research resource persons are Rectors and former Rectors, Public Relations, Lecturers, Employees and students of Untirta. To check the data, interviews were conducted with media partners, local governments and industry. The results showed that Untirta Branding was built through visual identity and brand activation process. Untirta's external branding is carried out through good relations with local and national media. To get the benefits of publication, a publication barter strategy is used, participating in the reporting of partner events at local and national events.